N-PASS Versus mPAT in Assessment and Management of Neonatal Pain at Neonatal ICUs in Palestine - Elessi, Khamis; Abed, Shireen; Afifi, Tayseer Jamal; Utt, Rawan; Elblbessy, Mahmood; Obaid, Mohammed; Elhatal, Hassan Abu; Elbhaisi, Ahmed; Alsultan, Khaled; Samaan, Mosab; Mayadma, Rawnaq; Badran, Lama; et al. (International Journal of Innovative Research in Medical Science, 2019)
Background: Neonates frequently experience pain as a result of diagnostic or therapeutic interventions or as a result of a disease process. Neonates cannot verbalize their pain experience and depend on others to recognize, assess and manage their pain. Neonates may suffer immediate or long-term consequences of unrelieved pain. Accurate assessment of pain is essential to provide adequate management. Observational scales, which include physiological and behavioral responses to pain, are available to aid consistent pain management. Pain assessment is considered as the fifth vital sign. Objectives: Aims of the present study were (1) to compare two commonly cited neonatal pain assessment tools, Neonatal Pain, Agitation and Sedation Scale (N-PASS) and modified Pain Assessment Tool (mPAT), with regard to their psychometric qualities, (2) to explore intuitive clinicians' ratings by relating them to the tools' items and (3) to ensure that neonates receive adequate pain control. Methods: Two coders applied both pain assessment tools to 850 neonates while undergoing a painful or a stressful procedure. Each neonate was assessed before, during and after the procedure. The evaluation before and after the procedure was done using NPASS, while pain score during the procedure was assessed by mPAT. Analyses of variances and regression analyses were used to investigate whether tools could discriminate between the procedures and whether tools' items were predictors of pain severity. Results: Internal consistency, reliability and validity were high for both assessment tools. N-PASS tool discriminated between painful and stressful situations better than mPAT. There was no relation between the age of neonate and the pain score. Moreover, P-value was statistically significant between mPAT score and post procedural assessment score as well as between pre and post procedural assessment scores. Conclusion: Both assessment tools performed equally well regarding physiologic parameters. However, N-PASS makes it possible to assess pain during sedation. It was noticed that gaps exist between practitioner knowledge and attitude regarding neonatal pain.